Pengaruh Board Gender Diversity dan Dewan Komisaris Independen Terhadap Kinerja Keuangan pada Perusahaan Non-Keuangan yang Terdaftar di Bursa Efek Indonesia Periode 2020-2024 - Febrianti Mita Lutvyana; Rina Susanti (Indo Publishing, 2025)
The purpose of this study is to examine and analyze the significance of the influence of board gender diversity and independent commissioners, both partially and simultaneously, on the financial performance of non-financial companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The population in this study includes all non-financial companies listed on the Indonesia Stock Exchange for the 2020–2024 period. The sampling technique used was purposive sampling, resulting in a sample of 350 companies out of 852. The data analysis methods used include descriptive statistical analysis, classical assumption tests, panel data regression analysis, t-test, F-test, and the coefficient of determination (R²). he results of the study indicate the following regression equation: Y = 1.7096 + 1.5722 X1 + 3.0262 X2 + 1.2642 X3 + Year_Dummy + Sector_Dummy + e. The t-test results show that the indicator of female commissioners does not significantly affect financial performance (significance = 0.399 > 0.05), and the indicator of female directors also does not significantly affect financial performance (significance = 0.061 > 0.05). However, the independent commissioner indicator has a significant positive effect on financial performance (significance = 0.020 < 0.05). The F-test results show that board gender diversity (female commissioners and female directors) and independent commissioners simultaneously have a significant effect on financial performance, with a significance value of 0.000 < 0.05. The coefficient of determination (R²) is 7.43%, while the remaining 92.57% is influenced by other variables not examined in this study.